2015
DOI: 10.1038/srep09893
|View full text |Cite
|
Sign up to set email alerts
|

A novel caspase 8 selective small molecule potentiates TRAIL-induced cell death

Abstract: Recombinant soluble TRAIL and agonistic antibodies against TRAIL receptors (DR4 and DR5) are currently being created for clinical cancer therapy, due to their selective killing of cancer cells and high safety characteristics. However, resistance to TRAIL and other targeted therapies is an important issue facing current cancer research field. An attractive strategy to sensitize resistant malignancies to TRAIL-induced cell death is the design of small molecules that target and promote caspase 8 activation. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…For example, Bucur et al (2015) synthesized a small molecule that binds caspase 8 and enhances its activation when combined with TRAIL inducing apoptosis in Jurkat cells. Furthermore, Lin et al (2010) demonstrated that SMI-4a, a small molecule inhibitor of Pim kinases, kill a wide range of both myeloid and lymphoid cell lines with precursor T-cell lymphoblastic leukemia/lymphoma being highly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bucur et al (2015) synthesized a small molecule that binds caspase 8 and enhances its activation when combined with TRAIL inducing apoptosis in Jurkat cells. Furthermore, Lin et al (2010) demonstrated that SMI-4a, a small molecule inhibitor of Pim kinases, kill a wide range of both myeloid and lymphoid cell lines with precursor T-cell lymphoblastic leukemia/lymphoma being highly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…An attractive strategy to sensitize resistant malignancies to TRAIL-induced cell death is the design of small molecules that target and promote caspase-8 activation. Through an in silico screening some authors successfully found a small molecule activator of caspase-8 [ 79 ]. Experimental validation performed in multiple cell lines, such as leukemic and prostate cells, revealed that CaspPro small molecule promotes caspase-8 activation, caspase-3 activation and PARP cleavage, in the presence of TRAIL, leading to cell death [ 79 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, caspase 8 activation caused by the down-regulation of c-FLIP at the transcriptional or posttranslational levels underlies the mode of action of some TRAIL sensitizers [ 45 ]. Likewise, small molecules that bind and stabilize the caspase 8 homodimers can function as TRAIL stabilizers by promoting caspase 8 activation upon TRAIL stimulation [ 56 ]. Chemotherapeutic drugs synergize with TRAIL mainly through lowering the apoptotic threshold by up-regulating proapoptotic BH3-only proteins while down-regulating antiapoptotic BCL-2 proteins and/or IAPs [ 39 ].…”
Section: Trailmentioning
confidence: 99%